The Role of Corporate Accountability in Reducing State Revenue Losses Due to Tax Avoidance and Tax Evasion - Suryaman, David Harmaen; Hasibuan, Fauzie Yusuf; Suganda, Atma (Advances In Social Humanities Research, 2025)
Corporate tax avoidance and evasion significantly undermine state revenue. In Indonesia, although corporations are legally recognized as criminal subjects, enforcement remains weak, as liability is often imposed on individual executives rather than on the corporation itself. This study aims to analyze forms of corporate accountability in cases of tax avoidance and evasion and to assess the effectiveness of its application in reducing state revenue losses. This study employs a juridical-normative approach combined with comparative and empirical analysis. National and international legal sources, academic literature, judicial decisions, and data from the Directorate General of Taxes are examined to assess the effectiveness of corporate liability in reducing the tax gap. Findings reveal that weak enforcement encourages corporations to treat tax non-compliance as a rational cost-benefit decision. In contrast, experiences in the UK and Australia show that robust liability regimes, including Deferred Prosecution Agreements and reputational sanctions, significantly improve corporate tax compliance. The study contributes academically by strengthening the discourse on corporate criminal liability in taxation, and practically by offering policy recommendations to enhance Indonesia’s fiscal regime through proportional sanctions, reputational mechanisms, and stronger inter-agency coordination.